Participant experiences with a multipurpose vaginal ring for HIV and pregnancy prevention during a phase 1 clinical trial: learning from users to improve acceptability - Shapley-Quinn, Mary Kate; Song, Mei; Chen, Beatrice A.; Devlin, Brid; Luecke, Ellen; Brown, Jill; Blithe, Diana L.; Achilles, Sharon L.; van der Straten, Ariane (Frontiers in Reproductive Health, 2023)
Introduction With high concurrent global rates of HIV incidence and unintended pregnancy, there is a need to provide options beyond condoms to enable users to simultaneously prevent HIV acquisition and pregnancy. Multiple vaginal rings are in development as “MPTs” (multipurpose prevention technologies) as they are shown to provide several co-occurring benefits such as discretion, convenience, reversibility and user control. Methods In this Phase 1 trial of a 3-month MPT ring in the U.S., 25 participants (low-risk for HIV and pregnancy) were randomized to use the study ring for 90 days continuously or in 28-day cycles with 2-day removal periods in between. All participants completed in-depth interviews at the end of their study participation. Results Overall, the ring was well tolerated. Participants resoundingly endorsed the concept of an extended-use, dual-purpose vaginal ring, but reported too many functional challenges and side effects to endorse this particular ring. Participants assigned to the continuous regimen reported more positive experiences with ring use than those in the cyclic group. A minority of participants who experienced minimal side effects and did not experience challenges with vaginal retention of the ring found it appealing. However, the majority of participants experienced challenges (ring slippage, expulsions, side effects, vaginal bleeding changes) with product use that outweighed the potential benefits and led them to report that – in the future – they would not be interested in using this specific version of the ring in its current form. A subset expressed interest in using the current MPT ring under certain conditions (e.g., if fewer expulsions, less bleeding, higher risk for HIV/pregnancy). Discussion User feedback regarding participant experiences and challenges with the study ring was continuously shared with the product developer, underscoring the value of early-stage end-user feedback in product development.